Isotopic ecology and extirpation chronology of the extinct Lesser Antillean native rodent Antillomys rayi Brace et al. (2015). (1st October 2020) - Goedert, Jean; Cochard, David; Lorvelec, Olivier; Oberlin, Christine; Cuzange, Marie-Thérèse; Royer, Aurélien; Lenoble, Arnaud
Abstract: The Lesser Antilles is a string of islands stretching from Grenada in the south to Sombrero in the north, which was once home to at least 20 insular populations of native rodents scattered across the different islands. Despite their relative ubiquity on the archipelago, these now extinct rodents remain poorly understood. In Guadeloupe (Basse-Terre and Grande-Terre), Marie-Galante, Barbuda and Antigua, fossil specimens of a large Lesser Antillean native rodent have recently been described as a distinct species, Antillomys rayi Brace et al. 2015. In order to shed new light on the processes leading to the extinction of this species, we use stable carbon and oxygen isotopes to better constrain its ecology, along with a series of radiocarbon dates to narrow its last-occurrence date in Guadeloupe and Marie-Galante. First, we built a reference collection of present-day isotopic data based on carbon and oxygen isotopes from black rats captured in different natural environmental contexts of Guadeloupe. Here, we show A. rayi to have occupied multiple distinct environments ranging from semi-deciduous dry forest to seasonal evergreen or mountain forests. New direct radiocarbon dates obtained on fossil material considerably bring forward the last occurrence of A. rayi in Guadeloupe and Marie-Galante, making it roughly coincident with European contact. However, our new calibrated age intervals place the last occurrence of A. rayi no later than the 16th century AD. Taken together, our results suggest that A. rayi became exceedingly rare, if not extirpated, in Guadeloupe and Marie-Galante shortly after European contact. While the overexploitation of A . rayi by Amerindian populations and the deforestation by European colonists could have impacted A. rayi populations, the consequences (biological competition, disease) of the introduction of black rat most likely explains the early decline of A. rayi and its ultimate extirpation from the islands of Guadeloupe. Highlights: Stable isotopes indicate A. rayi occupied multiple distinct forested environments. Radiocarbon dates brings forward last occurrence of A. rayi to a period that roughly coincide with European contact. A. rayi became exceedingly rare in Guadeloupe and Marie-Galante shortly after the contact period. Introduction of the black rat most likely explains the early decline of A. rayi and ultimately its regional extirpation.